Diuretic activity of 3-(5-bromfuran-2-yl)-4-r-(4h)-1,2,4-triazole-5-thione, their S-derivatives and 2-(5-bromfuran-2-yl)-5-r'-thiazolo[3,2-b][1,2,4]triazole-6(5h)-ones - Ye. S. Pruglo; A. S. Gotsulya; O. I. Panasenko; Ye. G. Knysh (Zaporozhye State Medical University, 2015)
The aim of study was to investigate diuretic activity of 1,2,4-triazole derivatives which contain С5 atom 5-bromfuran-2-yl substituent in the 1,2,4-triazole nucleus, and to establish interrelation between chemical structure and diuretic action of 1,2,4-triazole derivatives. Methods and results. For the investigation of the diuretic activity were used 15 compounds, namely 3-(5-bromofuran-2-yl)-4-R-(4H)-1,2,4-triazole-5-thiones, their S-derivatives and 2-(5-bromofuran-2-yl)-5-R'-thiazolo[3,2-b][1,2,4]triazole-6(5H)-ones. During the study Ye. B. Berkhin's method has been used to establish the influence of the compounds on the renal excretory function. Conclusion. The most active substance among 1,2,4-triazole derivatives was morpholinium 2-((5-bromofuran-2-yl)-4-ethyl-1,2,4-triazole-3-ylthio)acetate.